Exploring factors militating effective Zakat management for poverty alleviation in Kano State Nigeria: Stakeholders perspective - Ibrahim Atah, Ummi; Ahmad Usman, Muhammad; Yusuf Ismail, Sani; Baffa Sani, Muhammad (Universitas Muhammadiyah Pontianak, 2026)
The rate of poverty in Kano State is still persisting due to the recent fuel subsidy removal and hyperinflation. It is estimated that over 10.5 million people, about 66.3 percent, are poor. In spite of the fact the state established the Zakat and Hubsi commissions in 2003 to combat poverty and inequality, limited progress has been witnessed. The question is why it is that Zakat cannot achieve its objective of reducing the poverty rate and gap between rich and poor in Kano State as it is done in Indonesia and Malaysia. The objective of the research is to explore the factors that militate against effective Zakat management for poverty alleviation in Kano State. To achieve the study objective, a qualitative method is adopted by conducting a semi-structured interview with three informants. The study findings revealed that inadequate funding and poor patronage, politicization of leadership of Zakat and Waqf institutions, lack of trust and confidence as well as lack of creativity and innovation as factors that militate effective management of Zakat in Kano State, Nigeria. The study recommended that the Zakat commission should be more proactive in tandem with the innovative approaches of other Muslim countries in the collection, distribution, and management of Zakat by adopting modern technology. This can help to improve public trust, confidence, and patronage. The Zakat commission should also be independent from political influence. It is evident that achieving an optimal level of Zakat management among Muslim communities has not been realized up till today, and there is a need for more research to explore various means to come up with the best alternative ways to address the problems hindering effective Zakat management in various locations among Muslim communities. This research is aimed at filling this gap by contributing to the literature.